2001
DOI: 10.1074/jbc.m006473200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Receptor-associated Protein 1 Is a Smad4 Chaperone

Abstract: Members of the transforming growth factor-␤ (TGF-␤)superfamily signal through unique cell membrane receptor serine-threonine kinases to activate downstream targets. TRAP1 is a previously described 96-kDa cytoplasmic protein shown to bind to TGF-␤ receptors and suggested to play a role in TGF-␤ signaling. We now fully characterize the binding properties of TRAP1, and show that it associates strongly with inactive heteromeric TGF-␤ and activin receptor complexes and is released upon activation of signaling. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 39 publications
3
69
0
3
Order By: Relevance
“…TRAP1 plays a role in the Smad-mediated signal transduction pathway, interacting with the common mediator Smad4 in a ligand-dependent fashion. While TRAP1 has only a small stimulatory effect on TGF-b signaling in functional assays, deletion of TRAP1 inhibits TGF-b signaling and impairs the interaction between Smad4 and Smad2 [49]. However, TRAP1 does not affect the phosphorylation of Smad2.…”
Section: Discussionmentioning
confidence: 94%
“…TRAP1 plays a role in the Smad-mediated signal transduction pathway, interacting with the common mediator Smad4 in a ligand-dependent fashion. While TRAP1 has only a small stimulatory effect on TGF-b signaling in functional assays, deletion of TRAP1 inhibits TGF-b signaling and impairs the interaction between Smad4 and Smad2 [49]. However, TRAP1 does not affect the phosphorylation of Smad2.…”
Section: Discussionmentioning
confidence: 94%
“…TGFBRAP1 to VPS39 exchange might further be regulated by proteins such as MON1-CCZ1 (Fig. 6B), which are recruited by CORVET, interact with VPS39, and act as activators of RAB7 (44 -46) and signaling pathways such as the TGF␤ pathway, which has been shown to intersect with TGFBRAP1 and VPS39 function (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TGF-b receptor-associated protein-1 (TRAP-1) was found to speci®cally interact with Smad4 and to aid in the recruitment of Smad4 to the TGF-b and activin receptor complex (Wurthner et al, 2001). TRAP-1 associates with the inactive TGF-b receptor complex, and upon receptor activation, TRAP-1 dissociates from the receptor complex and associates with Smad4.…”
Section: Regulation Of Smad Activation Tgf-b Receptor-induced Smad Acmentioning
confidence: 99%
“…The TRAP-1/Smad4 interaction is transient and disrupted by activated R-Smads. Wurthner et al (2001) suggested that TRAP-1 may function as a chaperone to reduce the auto-inhibitory interactions between N-and C-terminal domains of Smad4 and thereby facilitate the interaction of Smad4 with activated R-Smads.…”
Section: Regulation Of Smad Activation Tgf-b Receptor-induced Smad Acmentioning
confidence: 99%